Factors related to blood-based biomarkers for neurodegenerative diseases and their intergenerational associations in the Young Finns Study: a cohort study - Heiskanen, Marja A; Mykkänen, Juha; Pahkala, Katja; Juonala, Markus; Kähönen, Mika; Lehtimäki, Terho; Laitinen, Tomi P; Jokinen, Eero; Tossavainen, Päivi; Linko-Parvinen, Anna; Pallari, Hanna-Mari; Blennow, Kaj; et al. (Elsevier BV, 2026)
Background: Blood-based biomarkers (BBM) of neurodegenerative diseases are emerging as cost-effective tools in the differential diagnostics of Alzheimer's disease and other dementias. Scarce data exist about factors explaining BBM variation in population-based cohorts, and their intergenerational associations are unknown. This study aimed to characterise BBM distributions among a population-based cohort, investigate the association of a wide array of factors with BBM both in midlife and old age, and investigate intergenerational associations of BBM. Methods: We measured BBM detecting amyloid beta and tau pathologies, including amyloid beta 42, amyloid beta 40, and phosphorylated Tau (pTau)-217, as well as glial fibrillary acidic protein (GFAP) and neurofilament light chain (NfL) in the multigenerational Young Finns Study participants (n=1237, age 41-56 years) and their parents (n=814, age 59-90 years) using the Quanterix Simoa HD-X analyser. Standard statistical methods were used to examine the associations between BBM and age, sex, genetic factors, a plethora of cardiometabolic markers, liver and kidney function, and lifestyle factors, as well as their intergenerational associations. Findings: Increased age was associated with adverse BBM concentrations. Of the various investigated factors, the most robust associations towards adverse BBM concentration were found for APOE epsilon 4 carrier status among parents (amyloid beta 42:40 ratio, pTau-217, and GFAP) and high serum creatinine concentration in both generations (pTau-217, GFAP, and NfL). Several factors related to glucose metabolism and dyslipidaemia were negatively associated with all BBM, but adjusting for BMI diluted many of these associations. Statistically significant intergenerational correlations ranged from 020 to 033 and were mostly observed between mothers and offspring in pTau-217, GFAP, and NfL. No intergenerational correlations existed in amyloid beta 42:40 ratio. Interpretation: We identified several factors that might influence BBM concentrations, parental transmission being one of them. For reliable use of BBM in clinical practice, it is important to identify which factors directly link to amyloid beta and tau pathology and which factors influence BBM concentrations due to other physiological processes. Copyright (c) 2025 The Author(s). Published by Elsevier Ltd. This is an open access article under the CC BY-NC-NDlicense (http://creativecommons.org/licenses/by-nc-nd/4.0/)